Amniotic fluid stem cell exosomes: Therapeutic perspective. (16th January 2018) - Beretti, Francesca; Zavatti, Manuela; Casciaro, Francesca; Comitini, Giuseppina; Franchi, Fabrizia; Barbieri, Veronica; La Sala, Giovanni B.; Maraldi, Tullia
Abstract: It is widely accepted that the therapeutic potential of stem cells can be largely mediated by paracrine factors, also included into exosomes. Thus, stem cell‐derived exosomes represent a major therapeutic option in regenerative medicine avoiding, if compared to stem cells graft, abnormal differentiation and tumor formation. Exosomes derived from mesenchymal stem cells (MSC) induce damaged tissue repair, and can also exert immunomodulatory effects on the differentiation, activation and function of different lymphocytes. Therefore, MSC exosomes can be considered as a potential treatment for inflammatory diseases and also an ideal candidate for allogeneic therapy due to their low immunogenicity. Amniotic fluid stem cells (AFSCs) are broadly multipotent, can be expanded in culture, and can be easily cryopreserved in cellular banks. In this study, morphology, phenotype, and protein content of exosomes released into amniotic fluid in vivo and from AFSC during in vitro culture (conditioned medium) were examined. We found that AFSC‐derived exosomes present different molecules than amniotic fluid ones, some of them involved in immunomodulation, such transforming growth factor beta and hepatic growth factors. The immunomodulatory effect of AFSC's exosomes on peripheral blood mononuclear cells stimulated with phytohemagglutinin was compared to that of the supernatant produced by such conditioned media deprived of exosomes. We present evidence that the principal effect of AFSC conditioned media (without exosomes) is the induction of apoptosis in lymphocytes, whereas exposure to AFSC‐derived exosomes decreases the lymphocyte's proliferation, supporting the hypothesis that the entire secretome of stem cells differently affects immune‐response. © 2017 BioFactors, 44(2):158–167, 2018